Improved visualization of X-ray phase contrast volumetric data through artifact-free integrated differential images. (April 2021) - Massimi, Lorenzo; Savvidis, Savvas; Endrizzi, Marco; Olivo, Alessandro
Highlights: Differential X-ray phase contrast images are affected by stripes when integrated. Iterative integration prevents stripes but is too slow for large CT datasets. Wiener-based integration is fast and can integrate X-ray phase contrast CT datasets Abstract: Artifacts arising when differential phase images are integrated is a common problem to several X-ray phase-based experimental techniques. The combination of noise and insufficient sampling of the high-frequency differential phase signal leads to the formation of streak artifacts in the projections, translating into poor image quality in the tomography slices. In this work, we apply a non-iterative integration algorithm proven to reduce streak artifacts in planar (2D) images to a differential phase tomography scan. We report on how the reduction of streak artifacts in the projections improves the quality of the tomography slices, especially in the directions different from the reconstruction plane. Importantly, the method is compatible with large tomography datasets in terms of computation time.